2019
DOI: 10.3390/su11092595
|View full text |Cite
|
Sign up to set email alerts
|

Using Native Vegetation Screens to Lessen the Visual Impact of Rural Buildings in the Sierras de Béjar and Francia Biosphere Reserve: Case Studies and Public Survey

Abstract: Tree screens have a demonstrated role in lessening the visual impact of buildings nonintegrated aesthetically by means of filtering façades. This is particularly useful on village fringes and in areas bordering urban green spaces. However, the role of other vegetal structure such as climber species, and their optimal percentage for façade filtering, have not been measured yet. The main objectives of present study were: (1) To guess if climber species have a similar positive role to lessen the visual impact of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Description of the Method Bearing in mind the studies mentioned in the Introduction, a proposal for measuring visual impact based on the initial study by García et al [11] is shown in Table 1. In this case, we used 40% increments in vegetation screening, according to the results of Garrido et al [30]. Two screening classes were established: 0-40% and 40-80%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Description of the Method Bearing in mind the studies mentioned in the Introduction, a proposal for measuring visual impact based on the initial study by García et al [11] is shown in Table 1. In this case, we used 40% increments in vegetation screening, according to the results of Garrido et al [30]. Two screening classes were established: 0-40% and 40-80%.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have taken a further step by attempting to determine the amount of screening necessary for sufficient integration as a percentage of the total built area [30]. One of the conclusions of Garrido et al [30] was that using vegetation with an intermediate degree of filtering in the frontal plane of a building (40-50%) increases the possibility of the perception of the façade improving from poor or very poor to at least acceptable. However, they did not determine a possible logarithmic relationship between increases in the percentage of vegetation concealment of buildings and their visual acceptability.…”
Section: Previous Impact Measurement Associated With the Present Studymentioning
confidence: 99%
“…In recent decades, rural buildings have proliferated in the rural environment, in many cases clashing with the surroundings [1][2][3][4][5][6][7][8]. Growing environmental awareness has created a need for more studies to analyze how the visual impact of buildings on the landscape can be minimized [9][10][11].…”
Section: Visual Impact Of Buildings On the Rural Landscapementioning
confidence: 99%
“…Polling measures observers' reactions to a series of visual proposals and may be the opinions of experts or surveys of the general public [37][38][39][40][41]. This tool has been widely applied and tested to validate hypotheses for visual impact analysis of buildings in the rural landscape [8,[42][43][44][45][46][47][48], and is the method used in this study.…”
Section: Public Participation In Visual Impact Analysismentioning
confidence: 99%
See 1 more Smart Citation